Infant motor development - Piek, Jan P. PhD
Infant motor development is the first resource to concentrate on motor development in infancy-the stage in which the greatest qualitative changes in the life span occur. This groundbreaking text combines theory with application to provide the most recent current account in infant motor ability and disability-including the latest prenatal research-all in one comprehensive resource. Infant motor development is organized into four parts covering theory, research, assessment, and intervention. It integrates information from a variety of disciplines to encourage a broad understanding of infant motor development. Topics include the development of voluntary movements such as posture, stability, balance, and orientation; manual control of reaching and grasping; locomotor control of creeping and walking; the unique difficulties faced by premature infants; and an examination of two disabilities with devastating consequences to motor control: cerebral palsy and Down syndrome